55.7k views
4 votes
(-3/2x4/5)+(9/5-10/3)-(1/2x3/4)

User Nablex
by
5.0k points

2 Answers

7 votes

will solve the equation separately and will add together


-3/2*4/5=-12/10


9/5-10/3=27-50

here i have taken the common denominator so the denominator becomes 50


-1/2*3/4=-3/8

now we have to add these three terms


-12/10-23/50-3/8=-240-92-75/200=-407/200

here i have taken common denominator for 5,10 and 8

will get 200 as common denominator .so the final expression will be -407/200

User David Kassa
by
5.3k points
2 votes


\left ( (3)/(2)* (4)/(5) \right )+\left ( (9)/(5)- (10)/(3) \right )-\left ( (1)/(2)* (3)/(4) \right )

In the first parenthesis, multiply the numerators so we get -12 and after multiply the denominator we will get 10

So the fraction in the first parenthesis will be
\left ( (-12)/(10) \right )

To solve the 2nd parenethesis, find the LCD of the denominator.

So the LCD of 5 and 3 = 15,

Now make the each denominator same as that of LCD.

So the new fractions in the 2nd parenthesis =
(\left ( (27)/(15)- (50)/(15) \right ) =
\left ( (-23)/(15) \right )

In the third parenthesis, multiply the numerators so we get 3 and after multiply the denominator we will get 8

So third parenthesis =
\left ( (3)/(8)\ \right )

=
\left ( (-12)/(10) \right ) + \left ( (-23)/(15) \right ) -\left ( (3)/(8)\ \right )

LCD of 12,15 and 8 is 120

=
\left ( (-144)/(120) \right ) + \left ( (-184)/(120) \right ) -\left ( (45)/(120)\ \right )

=
\left ( (-373)/(120) \right )

User Max Shron
by
5.2k points